ChemInform Abstract: A New Copper Borophosphate with Novel Polymeric Chains and Its Structural Correlation with Raw Materials in Molten Hydrated Flux Synthesis. Issue 11 (18th March 2014) - Duan, Ruijing; Liu, Wei; Cao, Lixin; Su, Ge; Xu, Hongmei; Zhao, Chenggong
Abstract The new compound Cu3[B2P3O12(OH)3] is synthesized by the molten hydrated flux method from a mixture of CuCl2·2H2O, NH4H2PO4, and H3BO3 in the molar ratio 1:1:10 (autoclave, 443 K, 7 d).